Laboratory tests and finite element simulations to model thermally induced reflective cracking of composite pavements. Issue Volume 19:Issued 3(2018) (4th March 2018) - Ban, Hoki; Im, Soohyok; Kim, Yong-Rak; Jung, Jong Suk
Abstract: This study presents a mechanistic pavement modelling approach to predict the performance and damage characteristics of composite pavements at low-temperature conditions. To meet the research objective, laboratory tests were incorporated with mechanistic finite element modelling. A typical composite pavement structure where an asphalt overlay is placed on cement concrete layer was selected and modelled by considering environmental conditions and paving materials of individual layers. Thermally induced reflective cracking of asphalt overlay was predicted and analysed by conducting finite element simulations incorporated with cohesive zone fracture. Parametric analyses were also conducted by varying pavement geometry and material properties, which could lead to helping pavement designers and materials engineers understand the mechanical sensitivity of design variables on the overall responses and performance characteristics of pavement structures. This better understanding is expected to provide roadway engineers with more scientific insights into how to select paving materials in a more engineered way and to potentially advance the current structural pavement design practices.